Effectiveness of video assisted teaching (vat) on knowledge and practice regarding personal hygiene among school children - STELLA SAGAYA MARY J (International Journal of Pharma and Bio Sciences, 2017)
A study was conducted to assess the effectiveness of Video Assisted Teaching (VAT) on the knowledge and practice regarding personal hygiene among children between 8-10 years in selected schools in areas at Madurai. The main objective of the study was to find out the effectiveness of video teaching on personal hygiene among children. Quasi experimental design with one group pretest and post test design was used to assess the knowledge and practice of personal hygiene. The study setting was Rajaji Government School, Sellur at Madurai. The sample size was 60. Simple random sampling technique was used to select the sample. Structured Questionnaire was used to assess the knowledge and Checklist was used to assess the practice regarding personal hygiene. Results showed that, there was improved knowledge and positive changes in the practice on personal hygiene among school children after video assisted teaching. Pre test knowledge score revealed that only 3% were having adequate knowledge; 58% were having moderately adequate knowledge and 42% were having inadequate knowledge. The school children gained knowledge after video assisted teaching the knowledge score revealed that 95% had adequate knowledge, 5% were moderately adequate and no one had inadequate knowledge. The effectiveness of health education was evident by the gained in knowledge and improvement in healthy practices after video assisted teaching program.